Secondary bile acid ursodeoxycholic acid alters weight, the gut microbiota, and the bile acid pool in conventional mice. - Jenessa A Winston; Alissa Rivera; Jingwei Cai; Andrew D Patterson; Casey M Theriot (PLoS ONE, 2021)
Ursodeoxycholic acid (commercially available as ursodiol) is a naturally occurring bile acid that is used to treat a variety of hepatic and gastrointestinal diseases. Ursodiol can modulate bile acid pools, which have the potential to alter the gut microbiota community structure. In turn, the gut microbial community can modulate bile acid pools, thus highlighting the interconnectedness of the gut microbiota-bile acid-host axis. Despite these interactions, it remains unclear if and how exogenously administered ursodiol shapes the gut microbial community structure and bile acid pool in conventional mice. This study aims to characterize how ursodiol alters the gastrointestinal ecosystem in conventional mice. C57BL/6J wildtype mice were given one of three doses of ursodiol (50, 150, or 450 mg/kg/day) by oral gavage for 21 days. Alterations in the gut microbiota and bile acids were examined including stool, ileal, and cecal content. Bile acids were also measured in serum. Significant weight loss was seen in mice treated with the low and high dose of ursodiol. Alterations in the microbial community structure and bile acid pool were seen in ileal and cecal content compared to pretreatment, and longitudinally in feces following the 21-day ursodiol treatment. In both ileal and cecal content, members of the Lachnospiraceae Family significantly contributed to the changes observed. This study is the first to provide a comprehensive view of how exogenously administered ursodiol shapes the healthy gastrointestinal ecosystem in conventional mice. Further studies to investigate how these changes in turn modify the host physiologic response are important.